EVALUATION OF BLENDED LEARNING IN HIGHER EDUCATION: A CASE STUDY - Mutawa, A. M. (PEOPLE: International Journal of Social Sciences, 2017)
Higher education institutions have been challenged by major changes in their environments and new trends in technology-supported teaching and new approaches in designing their curriculum. Blended e-learning is a combination of traditional classroom learning and online learning that includes some of the conveniences of online courses without losing face to face contact. This paper presents the point of view of instructors implementing Blended learning at the college of Engineering and Petroleum at Kuwait University using a Moodle-based platform called Online Course System OCS. Technology Acceptance Module (TAM) was used as a framework to generate questions for the survey.